2016
DOI: 10.1002/eco.1748
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the vegetation trends in a typical desertified watershed of northeast China over the past three decades

Abstract: Desertification is a serious environmental problem in north China that should be urgently addressed and prevented. Identifying the causes of vegetation trends that are closely related to desertification is prerequisite for a better control of desertification processes. In this study, the Xiliao River basin, a typical desertified watershed in northeast China, was selected as a case study. To partition the vegetation trends into climate-induced and human-induced trends, a linear regression model, piecewise regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The overall change trend of vegetation in the study period cannot truly reflect the changing characteristics of NDVI in different stages. Piecewise linear regression model is very powerful in extracting the turning point (TP) of NDVI time series, and has been widely used to evaluate the change trend of hydrology [61], NDVI, and climate over time [31,62]. In a single TP case, the calculation formula is as follows:…”
Section: Piecewise Linear Regression Analysismentioning
confidence: 99%
“…The overall change trend of vegetation in the study period cannot truly reflect the changing characteristics of NDVI in different stages. Piecewise linear regression model is very powerful in extracting the turning point (TP) of NDVI time series, and has been widely used to evaluate the change trend of hydrology [61], NDVI, and climate over time [31,62]. In a single TP case, the calculation formula is as follows:…”
Section: Piecewise Linear Regression Analysismentioning
confidence: 99%
“…Grassland in arid and semi‐arid regions is most sensitive to precipitation change (He et al , ), whereas forests, with its deep root systems, are less vulnerable. Cropland is impacted by climatic change, but human management such as irrigation could mitigate the negative effects (Wang et al , ). The relationships between NDVI and climate factors are discussed in more details in Section 4.4 and 5.1.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). In recent years, the relative impacts of climate change and human activities have been studied on the watershed ( Wang et al, 2016a ; Wang et al, 2016b ; Xu, Wang & Zhang, 2017 ), regional ( Xu, Wang & Zhang, 2016 ; Liu et al, 2018a ; Liu et al, 2018b ; Yan et al, 2019 ; Zheng et al, 2019 ) and national scales ( Thomas et al, 2014 ; Liu, Li & Li, 2015 ; Chen et al, 2019 ). Although there have been studies in Xinjiang ( Yang et al, 2017 ; Zhang et al, 2018 ), few studies have focused on the MBS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that the grassland NPP has increased as a result of the increase in precipitation and temperature and the different ecological conservation projects in some areas of China ( Zhou et al, 2015 ). Moreover, some studies have indicated that the grassland NPP has decreased as a result of overgrazing and the arid climate ( Wang et al, 2016a ; Wang et al, 2016b ). Climate change has different impacts on various grassland types in an MBS; therefore, future changes in grassland ecosystems in the future may become more complicated, and we must also consider the intensification of anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%